Sejarah Perang Hongi-Hinga Di Kerajaan Adonara Pada Masa Pemerintahan Raja Arakian Kamba - Hoda, Bergita Bita; Ande, Andreas; Rato, Flafius S (FLORESIENSIS, 2024)
The purpose of this study is to find out the history of the Hongi-Hinga war in the Adonara Kingdom during the reign of King Arakian Kamba. This research is a historical method. The results of the study show that (1) the Hongi-Hinga war that occurred in the Adonara Kingdom was motivated by three causes, namely the difference in siblings between Sabon Bele and Ola Masan who then both sought protection where Sabon Bele asked for protection from King Arakian Kamba and Ola Masan asked for protection from Kakang Hinga namely Luli Hada and Nama Sabon. (2) before the descent of both sides performed a bau lolon ritual to ask for strength and ancestral blessings. (3) the impact of the Hongi-Hinga war was a lot of casualties, the Hinga side had to pay war reparations in the form of 48 ivory and 5 lepo silver bars.